Overexpression of OsCIPK30 Enhances Plant Tolerance to Rice stripe virus - Liu, Zhiyang; Li, Xuejuan; Sun, Feng; Zhou, Tong; Zhou, Yijun (Frontiers in Microbiology, 2017)
Rice stripe virus (RSV) causes a severe disease in Oryza sativa (rice) in many Eastern Asian countries. The NS3 protein of RSV is a viral suppressor of RNA silencing, but plant host factors interacting with NS3 have not been reported yet. Here, we present evidence that expression of RSV NS3 in Arabidopsis thaliana causes developmental abnormalities. Through yeast two-hybrid screening and a luciferase complementation imaging assay, we demonstrate that RSV NS3 interacted with OsCIPK30, a CBL (calcineurin B-like proteins)-interaction protein kinase protein. Furthermore, OsCIPK30 was overexpressed to investigate the function of OsCIPK30 in rice. Our investigation showed that overexpression of OsCIPK30 in rice could delay the RSV symptoms and show milder RSV symptoms. In addition, the expression of pathogenesis-related genes was increased in OsCIPK30 transgenic rice. These results suggest that overexpression of OsCIPK30 positively regulates pathogenesis-related genes to enhance the tolerance to RSV in rice. Our findings provide new insight into the molecular mechanism underlying resistance to RSV disease.